IMPLEMENTASI TA’ZIR DALAM MENINGKATKAN KEDISIPLINAN SANTRI DI PONDOK PESANTREN AL MASRURIYYAH - Tasih, Amin; Said, Ali (Al-Misbah (Jurnal Islamic Studies), 2019)
Al Masruriyyah Islamic Boarding School is one of the huts of the Tebuireng foundation that is still hungry for discipline in obeying the rules of the cottage. Al Masruriyyah Islamic boarding schools apply ta?zir as a form of consequence for santri who violate the rules of the cottage. This study aims to describe and analyze the implementation of ta?zir in increasing the discipline of santri in Al Masruriyyah Islamic boarding schools. This study uses a qualitative research approach. Data collection techniques using the method of observation, interviews and documentation. The data obtained will be compiled by reducing/summarizing the data, then presenting the data and drawing conclusions.  Based on the research shows that: the implementation  of ta?zir carried out by the management and has been approved by the supervisor and caregivers for giving ta?zir every 2 weeks. The criteria for the distribution of ta?zir are 3 from the low, medium and heavy according to the mistakes that have been made. The procedure for giving ta?zir (1) is advised, (2) in ta?zir (3) to be called to Ndalem. The impact of the implementation of ta?zir is that there is a better change in the implementation of teaching and learning activities, obeying the rules, and discipline in worship activities to Allah SWT.